Correction: Meta-transcriptome Profiling of the Human-Leishmania braziliensis Cutaneous Lesion. - Stephen M Christensen; Laura A L Dillon; Lucas P Carvalho; Sara Passos; Fernanda O Novais; V Keith Hughitt; Daniel P Beiting; Edgar M Carvalho; Phillip Scott; Najib M El-Sayed; David M Mosser (Public Library of Science (PLoS), 2017)
[This corrects the article DOI: 10.1371/journal.pntd.0004992.].